Modeling Middle Devonian deposition in the Selwyn Basin, Northern Yukon. - Balgord, Elizabeth A. (My University, 2008)
A Ni-Mo-PGE sulfide deposit (NiMo) in norteastern Yukon occurs at the boundary between Ordovician-Early Devonian Road River and Middle Devonian Earn Group. This research investigated multiple genetic models for basin-wide mineralization. Electron microscopy (SEM and TEM) identified microbial structures, indicating a bacterial influence on sulfide precipitation.
Color poster with text, maps, and diagrams describing research conducted by Elizabeth Balgord, advised by J. Brian Mahoney, and Robert Hooper.
Keywords: Biomineralization; Sulfide minerals--Yukon; Sedimentation and deposition--Yukon; Posters; Nickel ores--Yukon; Geology, Stratigraphic--Yukon